Solid waste: the problema, basic concepts and some solution strategies (2019)
The present paper the result of the reference framework of the research Projectregistered in the research direction of the University Catholique of Pereiraentitled “Use of organic solid waste generated in the two whosale market ofPereira”. The paper denounces the continuos and uninterrupted growth ofsolid waste in the world and Colombia, its consequent negative impact onthe environment and the need to have basic conceptual agreements in thesearch for concepts, models, strategies and tools that configure environmentalmanagement that at least minimize the problem for humanity.